2022
DOI: 10.3390/s22041589
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Wearable Kinetic and Kinematic Sensors to Estimate Triceps Surae Work during Outdoor Locomotion on Slopes

Abstract: Muscle–tendon power output is commonly assessed in the laboratory through the work loop, a paired analysis of muscle force and length during a cyclic task. Work-loop analysis of muscle–tendon function in out-of-lab conditions has been elusive due to methodological limitations. In this work, we combined kinetic and kinematic measures from shear wave tensiometry and inertial measurement units, respectively, to establish a wearable system for estimating work and power output from the soleus and gastrocnemius musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Compared to horizontal displacement errors on the order of 0.5–1% of stride length [ 11 , 18 , 26 , 41 ], higher vertical errors around 1–2% are common [ 11 , 18 , 19 , 21 , 26 ]. Vertical error is especially important in interpreting the reconstructed movement because of the influence of ground incline on biomechanical outcomes such as limb and joint mechanics [ 42 , 43 , 44 , 45 , 46 ], muscle behavior [ 47 , 48 ], and energetic cost [ 49 ]. Moreover, the direction can be either rising or falling in different circumstances but tends to be consistent within specific bouts and behaviors.…”
Section: Related Workmentioning
confidence: 99%
“…Compared to horizontal displacement errors on the order of 0.5–1% of stride length [ 11 , 18 , 26 , 41 ], higher vertical errors around 1–2% are common [ 11 , 18 , 19 , 21 , 26 ]. Vertical error is especially important in interpreting the reconstructed movement because of the influence of ground incline on biomechanical outcomes such as limb and joint mechanics [ 42 , 43 , 44 , 45 , 46 ], muscle behavior [ 47 , 48 ], and energetic cost [ 49 ]. Moreover, the direction can be either rising or falling in different circumstances but tends to be consistent within specific bouts and behaviors.…”
Section: Related Workmentioning
confidence: 99%
“…In this study, we directly measured the Achilles tendon force in vivo during exosuit-assisted loaded walking. This direct measurement has numerous applications ( 22 , 23 ), including detection and mitigation of injury risk. Ground reaction forces increase proportionally with added load carriage weight ( 24 ), implying a corresponding increase in Achilles tendon force and a potential contributor to a heightened risk of injury ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have shown that the speed, squared, of a shear wave traveling along a tendon modulates with the axial force in the tendon (17). This technique has been applied to dynamic human movement, and changes in Achilles tendon force have been quantified during walking and running in various conditions (17)(18)(19)(20)(21)(22). Thus, because tensiometry is a direct measure of tendon force and independent of moment arms or muscle dynamics assumptions, it is feasible that shear wave tensiometry can be used to characterize the modulation of tissue forces with exosuit assistance.…”
Section: Introductionmentioning
confidence: 99%
“…There have been various approaches for collecting various types of data for the purpose of sensor fusion. First, monitoring is possible with a monitoring sensor module for healthcare in a residential environment, but it includes a sensor that can be used in forms of indoor services only [8,9]. Robotic multimodal sensors are used for manipulation [10].…”
Section: Introductionmentioning
confidence: 99%